BIIB021, an Hsp90 inhibitor, effectively kills a myelodysplastic syndrome cell line via the activation of caspases and inhibition of PI3K/Akt and NF-κB pathway proteins - LIN, SHENGYUN (D.A. Spandidos, 2014)
The novel orally available inhibitor of the molecular chaperone heat shock protein 90 (Hsp90), BIIB021, induces the apoptosis of various types of tumor cell in vitro and in vivo. However, the effects and mechanisms of this agent on myelodysplastic syndrome (MDS) cell lines remain unknown. The aim of this study was to investigate the effects of BIIB021 on SKM-1 cells (a MDS cell line) and examine its mechanisms of action. The results showed that BIIB021 inhibited the growth of SKM-1 cells effectively in vitro. The treatment of SKM-1 cells with BIIB021 resulted in the inhibition of cell growth through G0/G1-phase cell cycle arrest and induced apoptosis by activating caspase-3, -8 and -9. Furthermore, this study also demonstrated that the mechanisms of apoptosis in SKM-1 cells were associated with the suppression of the phosphatidylinositide 3-kinase/Akt and nuclear factor-κB signaling pathways. Therefore, the findings indicate a novel approach for the treatment of high-risk MDS.